MENTAL ILLNESS STIGMATIZATION IN TERTIARY MEDICAL COLLEGES IN KENYA: THE ROLE OF MASS MEDIA CONTENT - Maina J. Kamau (PT. Radja Intercontinental Publishing, 2023)
Stigmatization of the mentally ill persons has been one of the derailing factors on the gains made in fighting mental disorders. This stigmatization has seen escalation of the mental illness related effects such as school dropouts, suicide, substance abuse among other consequences as victims eschew seeking treatment for fear of stigmatization. On the other hand, mass media content through the framing of messages and how the communication on mental health issues has been portrayed, play integral role in shaping the public opinion on mental illness. This study therefore sought to examine the role played by mass media content on the stigmatization of mental illness among college students in Kenya Medical Training College. Using a descriptive research approach, the study through a questionnaire surveyed 384 students drawn from a population of 51045 students at the college. The data was analysed using descriptive and inferential statistics through SPSS. The findings revealed that the mass media content significantly influenced mental illness stigmatization among the college students. A conclusion was drawn that the failure by the mass media content to frame mental health issues in a clear and articulate manner, and lack of priming of the mental health-related issues contributed to increased ignorance and stereotyping of the mentally ill persons. It is therefore recommended that the media practitioners and stakeholders have a role to play in eradicating the stigmatization of the mentally ill persons by priming the mass media content on mental issues at the prime time just like other issues, and framing the content on mental health in an articulate manner that is more understandable. More time should also be allocated to mental health issues in the mass media content in order to create more awareness and eradicate the stigmatization.